Identifikasi Mikoriza Abuskula Secara Mikroskopis pada Rhizosfer Beberapa Jenis Rumput-rumputan dan Tanaman Kakao (Theobroma cacao L.) - NI KADEK SINTYA DEWI; I GEDE PUTU WIRAWAN; MADE SRITAMIN (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2014)
ABSTRACT Identification of Arbuscular Mycorrhiza through Microscopis Methode in Rhizosfer of Several Grass and Cacao ( Theobroma cacao L.) Arbuscular mycorrhiza fungi that live in a symbiotic mutualism with plant roots and helps the absorption of plant nutrients, and also able to live in various places. The study aimed to identifiy arbuscular mycorrhiza through microscopic methode in rhizosfer of several grass and cacao was conducted from December 2013 to March 2014. The method used in this study were spore isolation by wet sieving and root staining techniques. The results showed that arbuscular mycorrhiza spores and structures found in Imperata cylindrica L. are 2 types spores of genus Glomus (Glomales: Glomeaceae) with vesicular and hyphae structures. The presence of spores and structures in Paspalum notatum are Acaulospora (Glomales: Acaulosporaceae) and genus Gigaspora (Glomales: Gigasporineae) with arbuscular, vesicular and hyphae structure. Spores and structures of mycorrhiza found in the Pennisetum purpureum are 3 types of the genus Glomus with hyphae and arbuscular structure. Spores and structures mycorrhiza in the Cyperus rotundus are 1 type spore of the genus Gigaspora and 2 types of spores Glomus with internal hyphae structure. While spores and mycorrhiza structures in the cacao are 2 types spore of the genus Glomus with hyphae and vesicular structures. Keywords: Glomus, Gigaspora, Acaulospora, Arbuscular Mycorrhiza Structure